Electrochemical detection of single micelles through 'nano-impacts' - Toh, H; Compton, R (Royal Society of Chemistry, 2015)
A new class of 'soft' particles, micelles, is detected electrochemically via 'nano-impacts' for the first time. Short, sharp bursts of current are used to indicate the electrical contact of a single CTAB (cetyltrimethylammonium bromide) micelle with an electrode via the oxidation of the bromide content. The variation in CTAB concentration for such 'nano-impact' experiments shows that a significant number of 'spikes' are observed above the CMC (critical micelle concentration) and this is attributed to the formation of micelles. A comparison with dynamic light scattering is also reported.